MODELLING OF CENTRALIZED TWO-PHASE LOCKING WITH INTEGRATED MECHANISM OF TIMESTAMPS BY THE “WAIT – DIE” METHOD - Milev, Aleksandar; Vasileva, Svetlana (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
This paper presents an algorithm for two-phase locking (2PL) in which deadlocks of distributed transactions for distributed database management systems (DDBMS) are avoided. The method of timestamps is chosen for solving deadlocks and the centralized 2PL algorithm is implemented in DDBMS. The „wait - die” strategy of timestamps mechanism for deadlocks avoiding is presented in this paper. The simulation results of modeling “wait-die” algorithm are given by using GPSS World Personal Version for two and three elements length of distributed transaction.